Evolution of People’s Multiparty Democracy: Political Language, Ideological Adaptation, and Democratic Transformation in Nepal - Dhakal, Tika Prasad (State, Society and Development: PMPD Perspectives, 2026)
This article reconceptualizes the historical evolution of People’s Multiparty Democracy (PMPD), a political theory developed by Madan Bhandari. Drawing on a concentric qualitative framework of historical materialism, the sociology of knowledge, and Cambridge School contextualism, the study explores PMPD as an evolving ideological formation rather than a static doctrine. The analysis demonstrates how each layer of this evolution naturally succeeded the previous one through a sequential process of ideological development. Materially, it emerged from Nepal’s semi-feudal conditions, acknowledging democratic transformation as a necessary historical prerequisite for a socialist transition. These structural parameters were amplified by the post-Soviet crisis, during which PMPD operated as a sociology-of-knowledge mechanism for ideological maintenance, preserving a distinct Left identity within a pluralist framework. At the tactical level, this reorientation was accelerated through deliberate Cambridge School rhetorical innovations that embedded constitutionalism, competition, and popular sovereignty within a socialist vocabulary. This experimentation eventually created a democratic-socialist precedent that shaped the environment for the Maoist movement’s entry into peaceful politics following the 2006 peace process. PMPD is best analyzed as a historically situated process of ideological adaptation rather than as a capitulation to liberal hegemony. The article concludes by examining its contemporary challenges, warning of a twin crisis currently facing PMPD, navigating an increasingly hostile global order reminiscent of the 1990s while simultaneously confronting internal decay driven by corruption, expensive elections, and entrenched patronage networks.